KORELASI MINYAK-BATUAN INDUK UNTUK MENENTUKAN ASAL MINYAK DI CEKUNGAN JAWA TIMUR BAGIAN BARAT - Wiloso, Danis Agoes (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
The research area is located in the western part of the East Java Basin which is still a question about the origin of oil in the research area. Data on two oil seepage (Kedung Jati and Galeh oil seepage) and source rock from Rembang-1 drilling wells were tested based on normal alkanes, sterane (m/z 217) and triterpane (m/z 191), then compared to oil seepage and source rock. Oil-rock correlation based on normal alkane distribution, triterpane appearance (m/z 191) and sterane (m/z 217) of two oil seepage and source rock extraction from the Rembang-1 well show a positive correlation about oil seepage and source rock from the Ngimbang Formation, so it is estimated that the seepage of Kedungjati and Galeh oil is produced from the Ngimbang Formation.